2019
DOI: 10.21873/invivo.11706
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the CRP–to–Albumin Ratio for Patients With Pancreatic Cancer After Curative Resection: A Retrospective Single Center Study

Abstract: Background/Aim: Prognostic factors like the CRP-to-albumin ratio (CAR) represent potential predictors for survival of pancreatic cancer patients. We aimed to investigate the prognostic strength of the CAR for overall survival of patients with pancreatic cancer undergoing pancreatic resection. Patients and Methods: Data from a total of 202 patients with pancreatic adenocarcinoma who had undergone curative pancreatic resection were subjected to a retrospective review. Overall survival was calculated according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Seventeen studies were excluded after full-text review for insufficient data (n = 13), recruiting overlapping patients (n = 2), not focusing on pancreatic cancer (n = 1), and lack of pretreatment CAR measurement. Finally, the meta-analysis included a total of 11 studies 14 -24 comprising 2271 patients. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies were excluded after full-text review for insufficient data (n = 13), recruiting overlapping patients (n = 2), not focusing on pancreatic cancer (n = 1), and lack of pretreatment CAR measurement. Finally, the meta-analysis included a total of 11 studies 14 -24 comprising 2271 patients. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies 15,16,19,22 -24 reported the relevance of CAR and clinicopathological characteristics including sex (male vs female), tumor location (head vs body or tail), disease stage (metastasis vs locally advanced), and pN stage (N1 vs N0). As shown in Figure 4 and Table 3, the pooled data indicated that high pretreatment CAR was associated with male sex (OR = 1.38, 95% CI = 1.10-1.74, P = .006) but not tumor location (OR = 0.93, 95% CI = 0.72-1.20, P = .582), disease stage (OR = 0.70, 95% CI = 0.17-2.90, P = .623), or pN stage (OR = 1.26, 95% CI = 0.42-3.77, P = .675).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations